Oxybutynin: an overview of the available formulations - McCrery, Rebecca J (Dove Medical Press, 2006)
Overactive bladder (OAB) is a common problem presented to by physicians. Standard treatment with antimuscarinic medication is directed at suppressing involuntary detrusor contractions by blocking the binding of acetylcholine to muscarinic receptors in the bladder. Oxybutynin chloride is the first of several antimuscarinic medications to be marketed for OAB. Although efficacious for treating OAB symptoms, the side effects and suboptimal dosing regimen decrease its utility. To improve patient compliance and tolerability, alternative delivery systems for oxybutynin have subsequently been developed and include a once-daily formulation and a transdermal system. The currently available formulations of oxybutynin are the subject of this review.